Dinamika Kepribadian Amarah, Lamawah, dan Mutmainnah serta Relevansinya dengan Struktur Kepribadian Sigmund Freud - Mushodiq, Muhamad Agus Mushodiq; Andika Ari Saputra (Kuras Institute, 2021)
This paper aims to explore the dynamics of personality influenced by lust in Islamic psychology and its relevance to Sigmund Freud's personality structure. To explore the topic, the authors use qualitative literature research with descriptive analysis. The results of current study are. First, the three kinds of human lust in the Qur'an which include anger, lawwamah, and mutmainnah are psychic energies that determine a person's behavior as applicable in Sigmund Freud's psychoanalysis. Second, the relevance between lust and Id lies in their primitive nature as basic lust for humans. In Islam, lust for anger has a negative connotation if it is not enhanced in the realm of lawwamah lust and mutmainnah lust. Whereas in Freud's theory, Id is more neutral because Id is the basis or foundation of personality that encourages humans to think logically and rationally at the level of ego and super ego. Besides, anger and Id are driven by human unconsciousness to fulfill their physical needs. Third, the relevance between the lust of lawwamah and Ego lies in rationality and logic in determining attitudes. Lust for lawwamah is very synonymous with realization. A person's consciousness which is dominated by the lust of lawwamah and the ego is still in a subconscious level. Fourth, the relevance between lust mutmainnah and superego lies in controlling attitudes based on applicable rules or norms. In Islam, there are syariah (laws) that must be considered in taking a position in the realm of Id, and Ego. By practicing the syariah, a person is declared to have full awareness.